Genetic variation of ten Iraqi wheat genotypes using (SSR) markers and morphological characterization - Jameel Thamir AL-Tamim, Attyaf i; Abdul Hussein Al–Bdairi, Nidhal; kadem Farhood AL- Ghufaili, Melath; .A .Guda, Muthik; Shalaka Jawad Karim, Haider; Al-asadi, Sajjad (Al-Kufa University Journal for Biology, 2016)
The current study based on using morphological traits and simple sequence repeat(SSRs) markers to study variation among ten Iraqi wheat genotypes.  Primers  wmc596 and  wmc603 produced  three alleles distributed between one in wmc596 and two in wmc603 with an average number of 1.50 allele  per locus . Primer wmc603 was more  informative  than wmc596 as produced PIC reached  0.3750. Morphological traits including whole plant ( dry weight , height ,leaf number ,leaf area and branches number) , spike( dry weight ,length and number) and weight of 100 grain used for cluster analysis .Cluster analysis depending on  morphological traits grouped wheat genotypes among  two major groups , the first included only Faris genotype while the other large one included the rest genotypes which further divided in to two sub clusters. Genotypes  identification  and studying genetic variation produce an efficient tool for genotypes selecting in breeding programs.